2021
DOI: 10.1186/s12986-020-00538-9
|View full text |Cite
|
Sign up to set email alerts
|

Combined Lycium barbarum polysaccharides and C-phycocyanin increase gastric Bifidobacterium relative abundance and protect against gastric ulcer caused by aspirin in rats

Abstract: Background Non-steroidal anti-inflammatory drugs such as aspirin are used for the treatment of cardiovascular disease. Chronic use of low-dose aspirin is associated with the occurrence of gastric ulcer. The aim of this study was to investigate the healing potential of Lycium barbarum polysaccharides (LBP) from Chinese Goji berry and C-phycocyanin (CPC) from Spirulina platensis on gastric ulcer in rats. Methods Male Sprague–Dawley rats were divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 62 publications
1
15
0
Order By: Relevance
“…It has been suggested that this anatomic part of the human body could be considered as a bioreactor in which an extremely dense microbial consortium is performing various functions that are important for systemic health ( 1 ). Gut microbiota is comprised of members of all three domains of life—Bacteria, Archaea and Eukarya; however, large individual differences hamper the complete description of the ecosystem ( 2 ). Despite its complexity and variability, recent research has clearly shown that interaction between gut microbiota and undigested food components, as well as medicaments, can yield various metabolites that could promote or jeopardize human health ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that this anatomic part of the human body could be considered as a bioreactor in which an extremely dense microbial consortium is performing various functions that are important for systemic health ( 1 ). Gut microbiota is comprised of members of all three domains of life—Bacteria, Archaea and Eukarya; however, large individual differences hamper the complete description of the ecosystem ( 2 ). Despite its complexity and variability, recent research has clearly shown that interaction between gut microbiota and undigested food components, as well as medicaments, can yield various metabolites that could promote or jeopardize human health ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2019) reported that dietary LBPs improved intestinal morphology and nutrient absorption in young rats. In addition, Hsieh et al (2021) indicated that dietary LBPs improved gastric microbiota by increasing gastric Bifdobacterium levels in rats. Therefore, these and our evidence may be mediated by the promotional effects of LBPs on growth performance.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, the potential healing effect of the Chinese goji berry extract on aspirin-induced gastric ulcer in rats was investigated. Based on reduced lipid peroxidase malondialdehyde levels by 78%, the berry extract was confirmed to have the potential to heal in vivo gastric ulcers [ 61 ]. From a different point of view, the gastric damage of maqui berry extract, as a side effect potential, was investigated when applied with the purpose of its antinociceptive effect in mice.…”
Section: Health Effects Of Berriesmentioning
confidence: 99%